Prosecuting War Crimes in Domestic Level: The Case of Bangladesh - Rahman, Mizanur; Billah, SM Masum (Northern University Journal of Law, 2014)
Theodore Meron, the former Judge of the International Criminal Tribunal for the former Yugoslavia (ICTY) in an Article has posed a pearl question: Why do atrocities like massacres recur irrespective of claimed success of prosecuting the perpetrators at Nuremburg and the like? DOI: http://dx.doi.org/10.3329/nujl.v1i0.18522 Northern University Journal of Law Vol.1 2010: 14-23